MANAJAMEN BUDAYA SEKOLAH BERBASIS PEMBIASAAN HARIAN TEMATIK UNTUK INTERNALISASI KEDISIPLINAN DAN CAPAIAN AKADEMIK (STUDI KASUS DI SMK NEGERI 15 GARUT) - Warta, Waska; Maulana, Bagja; Susanti, Hetty; Kosirin, Iis (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the implementation and effectiveness of a thematic daily habituation program implemented systematically from Monday to Friday during school entry hours at SMK Negeri 15 Garut. This research was driven by the urgency of vocational education institutions to produce graduates who are not only technically competent but also possess professional work ethics and strong character. Utilizing a qualitative descriptive approach within the framework of Educational Administration, data were gathered through participant observation, documentation of discipline logs, and tracking student academic progress. The data analysis followed an interactive model comprising data reduction, data display, and conclusion drawing. The results demonstrate that structured habituation serves as an effective preventive intervention, producing a "ripple effect" that optimizes student learning readiness. The systematic implementation of the five core pillars Nationalism (Monday), Cognition Numeracy (Tuesday), Ecology (Wednesday), Literacy (Thursday), and Spirituality (Friday) significantly improved student compliance and expanded both academic capabilities and soft skills. This study concludes that school culture management through well-planned, routine-based standard operating procedures is vital for shaping behavioral outcomes and simulating industrial work culture in vocational education environments.